Increased Nitrogen Loading Boosts Summer Phytoplankton Growth by Alterations in Resource and Zooplankton Control: A Mesocosm Study - He, Hu; Chen, Kunquan; Du, Yingxun; Li, Kuanyi; Liu, Zhengwen; Jeppesen, Erik; Søndergaard, Martin (Frontiers in Environmental Science, 2021)
The effectiveness of controlling nitrogen (N) to manage eutrophication of aquatic ecosystems remains debated. To understand the mechanisms behind phytoplankton growth in shallow lakes (resource and grazing effects) under contrasting N loading scenarios, we conducted a 70-day mesocosm experiment in summer. The mesocosms contain natural plankton communities deriving from a 10-cm layer of lake sediment and 450 L of lake water. We also added two juvenile crucian carp (Carassius carassius) in each mesocosm to simulate presence of the prevailing omni-benthivorous fish in subtropical lakes. Our results showed that N addition increased not only water N levels but also total phosphorus (TP) concentrations, which togeth-er elevated the phytoplankton biomass and caused strong dominance of cyanobacte-ria. Addition of N significantly lowered the herbivorous zooplankton to phytoplank-ton biomass ratio and promoted the phytoplankton yield per nutrient (Chl-a : TP or Chl-a : TN ratio), indicating that summer N addition likely also favored phytoplank-ton growth through reduced grazing by zooplankton. Accordingly, our study indi-cates that summer N loading may boost eutrophication via both resource and grazing control in shallow lakes. Thus, alleviation of eutrophication in shallow eutrophic lakes requires a strategic approach to control both nutrients (N & P) appropriately.